SCHOOL SUPERINTENDENT ASSESSMENT MODEL IN THE OFFICE OF THE MINISTRY OF RELIGION (STUDY OF THE OFFICE OF THE MINISTRY OF RELIGION IN KUDUS REGENCY, CENTRAL JAVA) - Mukhamad Saekan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Assessment is a process to determine the ability of an object. Judging from the aspect of the instrument, the results of a comprehensive assessment need to be carried out using both physical and non-physical instruments. Judging from the assessing elements, a comprehensive assessment needs to be carried out by several elements, so that it will produce complete and comprehensive data. Judging from the elements being assessed, the ideal assessment is one that is able to know and assess the competence of the object being assessed. Performance appraisal is a process to find out a job that is carried out routinely (periodically) which is intended to find out the shortcomings and weaknesses of the object being assessed. Performance appraisal for school supervisors needs to be carried out with instruments that are not only physical, but also with non-physical instruments. The school supervisor's assessment also needs to be assessed not only by one element but also by several elements that are related to the performance of the school/madrasah supervisor. The school supervisor's assessment also needs to be carried out based on the competence possessed by the school supervisor. Performance appraisal can be done in various types/methods, including (a) individual assessment, namely the assessment process to determine personal performance carried out by school/madrasah supervisors. (b) formal assessment of the bureaucracy, namely the assessment process carried out by means of a formal bureaucratic document, namely the Employee Achievement Assessment List (DP3). (c)collaborative assessment, namely a process of evaluating/assessing the performance of school/madrasah supervisors which is carried out by involving many elements that have the relevance of authority. (d) competency assessment, namely the assessment process is carried out based on the competence possessed by the object being assessed. Assessment of the performance of school supervisors in the office of the Holy Ministry of Religion is not only carried out in a formal bureaucratic manner, but is carried out in various ways so as to be able to produce the performance of school supervisors as a whole and comprehensively..